A modified ISO 13528 robust analysis (Algorithm A) that takes measurement uncertainty into account. (November 2017) - Carobbi, Carlo
Highlights: Modified ISO 13528 robust analysis in order to incorporate measurement uncertainty. Uncertainty of the reference value reflecting technical capabilities and state of knowledge. Validity of the zeta-score performance statistic not impaired. Positively affected z-score performance statistic. Abstract: A new approach is here presented for the calculation of a robust reference value and the corresponding robust standard uncertainty to be used in proficiency test data analysis. The proposed method takes into account both the spread of the measured values and the measurement uncertainty declared by the participants in the proficiency test, while the robust standard ISO 13528 methods take only the measured values into account, neglecting measurement uncertainty. The zeta- and z-score performance statistics are consequently modified to adapt the proposed method. Examples of application of the method to actual proficiency test data are offered permitting to appreciate its validity and to facilitate insight.